Changes in the salivary oxidative status in individuals with temporomandibular disorders and pain - Claudyane de Almeida; José Miguel Amenábar (Elsevier, 2016)
Temporomandibular joint disorders are quite common among the general public. Free radicals may play a role in the pathogenesis of joint diseases, and the oxidative stress is an important aspect in the mechanism of TMDs. The use of new biotechnologies has enabled the use of saliva as a diagnostic method. This is the first paper that aims to investigate changes in the oxidative status, through saliva analysis, in individuals who suffer from temporomandibular disorder and pain. Sixty individuals, 54 women and 06 men, aged between 10 and 60, participated in this research. The questionnaire 'Research Diagnostic Criteria for Temporomandibular Disorders' (RDC/TMD) was filled out in order to determine the presence and the type of TMD, and the Visual Analogue Scale (VAS) was conducted in order to measure the pain perception caused by TMD. In addition, the total oxidant status (TOS), and the total antioxidant capacity (TAC) were measured, and the oxidative stress index (OSI) was calculated. The t-test and the Pearson Correlation Test were used with the significance level of p < 0.05. The TAC in individuals with TMD and pain was significantly reduced (p < 0.001). There was no difference regarding the levels of TOS (p = 0.765) between both groups. As a result, the OSI was significantly higher in the group TMD and pain (p = 0.011). There was no correlation between VAS, TAC, and TOS values. Within the limits of this study, oxidative changes seem to influence the pathogenesis of pain in TMDs.